Lactobacillus plantarum ZS62 Alleviates Alcohol-Induced Gastric Injury in Mice via an Anti-Oxidative Mechanism - Wu Y; Hu J; Long X; Pan Y; Mu J; Park KY; Zhao X (Dove Medical Press, 2021)
Ya Wu,1,2,* Jing Hu,3,* Xingyao Long,1,4 Yanni Pan,1,4 Jianfei Mu,1 Kun-Young Park,1,4 Xin Zhao1 1Chongqing Collaborative Innovation Center for Functional Food, Chongqing Engineering Research Center of Functional Food, Chongqing Engineering Laboratory for Research and Development of Functional Food, Chongqing University of Education, Chongqing, 400067, People’s Republic of China; 2College of Biological and Chemical Engineering, Chongqing University of Education, Chongqing, 400067, People’s Republic of China; 3Department of Pharmacy, Southwest Hospital, Army Medical University (Third Military Medical University), Chongqing, 400038, People’s Republic of China; 4Department of Food Science and Biotechnology, Cha University, Seongnam, 13488, South Korea*These authors contributed equally to this workCorrespondence: Kun-Young Park; Xin Zhao Tel +86-23-6265-3650Email kunypark@foods.ac.cn; zhaoxin@cque.edu.cnAim: Gastric mucosal injury is a typical characteristic of gastric diseases. The prevalence of gastric mucosal injury caused by alcohol has been on the rise, which has been considered a serious problem. The purpose of this study is to explore the protective effect on gastric injury of Lactobacillus plantarum ZS62 (LP-ZS62) isolated from naturally fermented yak yoghurt.Methods: We established a gastric injury model through alcohol and evaluated the protective effect of LP-ZS62 on gastric injury in mice. The injury to the gastric mucosa, histopathological sections, related biochemical indicators, and related genes were examined to evaluate the protective effect of LP-ZS62.Results: LP-ZS62 effectively alleviated alcohol-induced gastric injury according to visual observations of gastric tissue and pathological tissue sections. The experimental results revealed that LP-ZS62 decreased malondialdehyde (MDA) level, and elevated superoxide dismutase (SOD) and glutathione (GSH) levels in gastric tissues. Additionally, LP-ZS62 increased glutathione peroxidase (GSH-Px), prostaglandin E2 (PGE2), and somatostatin (SS) levels. LP-ZS62 also decreased inflammatory cytokines interleukin (IL)-1β, tumor necrosis factor-α (TNF-α) and IL-6 levels, and increased the anti-inflammatory cytokine IL-10 level. The quantitative polymerase chain reaction results showed that LP-ZS62 upregulated mRNA expression of nuclear factor E2-related factor 2 (Nrf2), copper/zinc superoxide dismutase (SOD1), manganese superoxide dismutase (SOD2), catalase (CAT), gamma-glutamylcysteine synthetase (GSH1), and glutathione peroxidase (GSH-Px).Conclusion: This study confirmed that LP-ZS62 alleviated alcohol-induced gastric injury by regulating antioxidant capacity. Therefore, LP-ZS62 could be developed as a probiotic product to treat alcoholic gastric injury.Keywords: Lactobacillus plantarum ZS62, alcohol-induced gastric injury, inflammation, antioxidant